Body Sizes in Nineteenth Century New Zealand: An Empirical Investigation using the NZ Contingents in the Second Boer war - Geoffrey Brooke; Lydia Cheung (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2019)
In this paper we report on the heights and weights of New Zealand soldiers who served in the Second Boer War (1899-1902). Adult heights are widely used as evidence on the standard of living. Interpreted as such, our results support the view that the standard of living in New Zealand was among the highest in the world at the turn of the twentieth century. One problem in using the heights of soldiers to make inferences about the population is the reliance on self-reported ages. When we use self-reported ages in our analysis we find that the youngest soldiers are also the shortest. This finding is common in the literature, and has been interpreted as evidence for a general decline in the standard of living. To explore the implication of using reported ages, we match 53% of the soldiers in our sample to their birth records to establish their true age. We document that young soldiers exaggerate their age and old soldiers under-state their age. When we use true ages in our analysis, the apparent shortness of the youngest soldiers disappears.
Keywords: O65; I10; N37; 330; stature; Second Boer War; historic birth records; nineteenth century New Zealand